(untitled) (Bangladesh Journal of Psychology, 2024)
Decision-making styles play an important role in overcoming the everyday challenges we face. Therefore, it is essential to have a psychometrically sound assessment tool to assess the decision-making styles we use. This study aimed to validate the Melbourne Decision-Making Questionnaire (MDMQ) in Bangla language and cultural context, addressing the lack of available measures for assessing decision-making styles used by the Bangladeshi people. In this study, data were collected from a sample of 300 university students (age mean = 21.20 years) who were selected using the convenience sampling technique. Confirmatory factor analysis supported the four-factor correlated model, as found in the original study. Discrimination indices of items in both classical test theory and item response theory approaches suggested that items could effectively discriminate between low scorers and high scorers in each subscale. Differential item functioning test results showed no preference for a specific gender. Each subscale significantly correlated with Big Five personality traits and life satisfaction. Overall, the results suggest the MDMQ Bangla as a psychometrically sound tool to assess decision-making styles used by Bangladeshi adults. This measure has practical utility for researchers and mental health practitioners, enabling a deeper understanding of decision-making styles among Bangladeshi people, their antecedent factors and their impact on daily life. Bangladesh Journal of Psychology, Vol. 24, December 2024, pp. 61-80